Sustainability Awareness, Engagement, and Perception of Indonesian High School Students during Sustainability Project Based Learning Implementation in Biology Education - Heru Setiawan; Hertien Koosbandiah Surtikanti; Kusnadi Kusnadi; Riandi Riandi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to evaluate students' sustainability awareness and engagement and to analyze students' perception of the ESD Project in Biology lessons at an Indonesian Senior High School. This study uses a Mixed Method research design combining quantitative and qualitative research methods. The participants were Year X students of a Senior High School in Jakarta in the 2022/2023 academic year. Survey, journal of reflection, semi-structured interview, observations, and documentation, were used to collect data. Finding: This research found that ESD Project in biology lessons develops Indonesian students' sustainability awareness and engagement. Students change their mindset from being unconscious to become more concerned with environmental issues. Several evidence of the consciousness in this research includes applying sustainability in the daily practice, doing real action by creating campaign videos. The awareness is also shown by their beliefs, values, and judgments in their reflective journal, including developing environmental literacy, changing into pro-environment, and positive attitude to protect the environment.Â Secondly, PjBL learning model in Biology lessons is meaningful for students by stimulating their cognitive and behavioral engagement. The most popular activity of the ESD Project is creating the design of clothes from waste. The implementation of ESD Projects has some challenges such as time consuming, and low self-regulation among Indonesian high school students. Implications for research, practice, and policy are discussed.Â